142 Advance Care Planning in Patients with Dementia: An Audit on End of Life Care in Hospital Deaths. (16th September 2019) - Sullivan, Rachel; Power, Clodagh; Greene, Elaine; Purcell, Roisin
Abstract: Background: End of life care (EOLC) planning is a difficult and often neglected area in dementia. Advanced care discussions play an important role in the planning of future care for patients with dementia. The NICE guidelines recommend that patients with dementia should be given every opportunity to discuss their wishes and preferences regarding their future care. The goal of our study was to explore the extent of EOLC planning in patients with dementia who died in hospital. Methods: Patients with dementia who died in a large tertiary referral hospital in 2017 were identified via the Hospital Inpatient Enquiry (HIPE) database. A retrospective chart review was completed examining the documentation of Advance Care Planning (ACP) and discussions around end of life care. Charleston Comorbidity Index (CCI) was used to predict 1 year mortality. Results: HIPE identified 49 patients with dementia who died in hospital. The average age was 84 and 53% were female. The commonest cause of death was respiratory (79.5%). Two thirds lived at home and 30% were nursing home residents. The mean CCI was 3.97 indicating 52% 1-year mortality, however only 34% were hospitalized in the last year. Only 14% had an ACP. Only 22% had resuscitation status recorded on admission. The majority had resuscitation status documented 15 days prior to death. In these cases 70% had clearly documented the discussion with family or patient and 84% documented ceilings of care 6 days prior to death. Palliative care were involved in 40% of cases. Two patients did not have resuscitation status documented prior to death and 3 received CPR. Conclusion: Our study highlights the urgent need to facilitate conversations around end-of-life care with people with dementia. Advance care planning reduces the use of burdensome treatments, ensures dignity and comfort is prioritized enabling patients to live well until they die.